APPLYING CWQI IN COASTAL WATERS OF DA NANG CITY, VIETNAM - Hoa, Ho Cong (Vietnam Journal of Marine Science and Technology, 2009)
Traditional reports on water quality typically consist ofcomplex variableby-variable, and water body-by-water body statistical summaries. This type ofinformation is ofvalue to water quality experts, but may not be meaningful to people who want to know about the state oftheir local water bodies and for managers and policy makers who require concise information about those water bodies [6]. Developing a water quality index is very necessary, it gives us an evaluation method allows water quality data to be compiled and reported in a consistent manner throughout people jurisdictions. Therefore, in 1970, Brown developed a water quality index (WQ!), and the Canadian scientists developed the Canada water quality index (CWQI) in 2001 . This report introduces the evaluation method ofwater quality by using the CWQJ and some initial results ofthe CWQJ application in coastal water quality ofDa Nang.